Low plasma triiodothyronine levels in heart failure are associated with a reduced anabolic state and membrane damage - Brenta, Gabriela (2011)
BACKGROUND: Low plasma triiodothyronine (T(3)) levels are considered a prognostic predictor of death in heart failure (HF) patients. AIM: To study an association between plasma T(3) levels and several cardiac, neurohormonal, and metabolic markers of HF. METHODS: A total of 133 ambulatory HF patients (114 males; mean age 63.2 years) with left ventricular ejection fraction <40% were enrolled. TSH, total tetraiodothyronine (T(4)) and T(3), N-terminal pro-brain natriuretic peptide (NT-proBNP), and other cardiac and metabolic parameters were measured. The lowest tertile of T(3) (group 1) was compared against the two upper ones (group 2). RESULTS: In simple logistic regression, the lowest T(3) tertile was associated with more advanced HF disease status: older (age: odds ratio (OR)=1.05; confidence interval (CI) 95% 1.01-1.09, P=0.004), lower functional capacity (walking test: OR=0.996; CI 95% 0.993-0.999, P=0.008), higher NT-proBNP (OR=1.64; CI 95% 1.19-2.27, P=0.003) and adiponectin levels (OR=1.07; CI 95% 1.02-1.11, P=0.004), lower DHEAS log-transformed (OR=0.50; CI 95% 0.31-0.80, P=0.004), and the presence of lower phase angle values as measured by body bioelectrical impedance analysis (OR=3.18; CI 95% 1.50-6.71, P=0.04) and worse renal function (OR=0.96; CI 95% 0.94-0.98, P=0.003). T(3) levels in the lowest tertile were independently associated with low phase angle values (OR=2.95, CI 95% 1.16-7.50, P=0.02) and the log transformation of DHEAS (OR=0.56; CI 95% 0.32-0.97, P=0.04). CONCLUSION: We have demonstrated an association between plasma T(3) levels in the lower range and other deranged hormonal and metabolic parameters in HF patients.